Selective Radionuclide Localisation in Primary Liver Tumours. Issue 3 (1994) - Novell, J. R.; Green, A. J.; Hilson, A. J. W.; Dusheiko, G.; Dick, R.; Hobbs, K. E. F.
Abstract : The therapeutic potential of 131 I-Lipiodol was investigated in 8 patients with cholangiocarcinoma (CCA) and 15 patients with hepatocellullar carcinoma (HCC). Patients received one or two doses of 131 I-Lipiodol via hepatic arterial injection. The mean total administered activity was 668 (SD 325) MBq in CCA and 953 (SD 477) MBq in HCC. One patient with CCA retained 131 I-Lipiodol. The cumulative radiation dose was 9.6 Gy to tumour, 6.4 Gy to liver and 1.5 Gy to lung. The patient remained asymptomatic with no evidence of tumour 30 months from the start of treatment, whereas the remaining 7 patients exhibited tumour progression. The mean survival in CCA was 11.6 (SD 14.5) months. All 15 patients with HCC retained 131 I with tumour: liver ratios of up to 30:1. The mean cumulative radiation dose was 34.7 (SD 32.4) Gy to tumour, 3.3 (SD 1.5) Gy to liver and 4.4 (SD 2.3) Gy to lung. The mean dose per administered activity was 3.8 (SD 4.1) cGy/MBq. Partial response (reduction in tumour size > 50%) was observed in 6 patients (40%). The mean survival was 7.1 (SD 6.0) months. 131 I-Lipiodol can deliver highly selective internal irradiation to foci of HCC with evidence of objective response and may be the treatment of choice for patients with cirrhosis and a small tumour.